Pulpal temperature increase with high-speed handpiece, Er:YAG laser and ultrasound tips - Mollica, Fernanda Brandão [UNESP]; Camargo, Fernanda Pelogia [UNESP]; Zamboni, Sandra Costa [UNESP]; Pereira, Sarina Maciel Braga [UNESP]; Teixeira, Symone Cristina [UNESP]; Nogueira Jr., Lafayette [UNESP] (FapUNIFESP (SciELO), 2008)
The aim of this study was to compare intrapulpal temperature increase produced by high-speed handpiece, Er:YAG laser and CVDentus ultrasound tips during cavity preparation. Thirty bovine mandibular incisors with an enamel/dentin thickness of 4 mm at buccal surface had their roots amputated and were allocated to the following groups (n=10): Group I- high-speed handpiece; Group II- noncontact Er:YAG laser (250 mJ/4Hz); and Group III- CVDentus ultrasouns tips. All devices were used with water cooling. Class V cavities were prepared to a depth of 3.5 mm, measured with a periodontal probe. A type T thermocouple was placed inside the pulp chamber to determine the temperature increase (°C), which was recorded by a data acquisition system ADS 2000 IP (Lynx Technology) linked to a notebook computer. Data were analyzed statistically by oneway ANOVA and Tukey's test (p=0.05). The mean temperature rises were: 1.10°C (±0.56) for Group I, 0.84°C (±0.55) for Group II, and 3.00°C (± 1.34) for Group III. There were no statistically significant differences (p>0.05) between Groups I and II, but both of them differed significantly from Group III (p<0.05). In conclusion, the use of Er:YAG laser and high-speed handpiece for cavity preparation resulted in similar temperature increase. Although ultrasound tips generated significantly higher intrapulpal temperature increase, it remained below the critical value of 5.5°C and may be considered safe for use.
Keywords: Dental cavity preparation; Dental pulp